Research on Chaozhou Community in Early Klang / 早年巴生潮州人社群初探 - SER, Wue Hiong (Journal of Chinese Literature And Culture 馬大華人文學與文化學刊, 2017)
Abstract Klang is the earliest region to be developed in Klang valley area. Among the numerous Chinese there, the Chaozhou dialect ethnic community is a minority. Since the Chaozhou migrants came to Klang at the end of 19th century, they have become a distinctive local community in Klang. They organized their association, participated in the construction of local Chinese culture and education, and also dominated the groceries and rice trading for a very long time in Klang. This paper, by combining both historical documents and field works for review the immigrant, original home, business feature, outlines the appearance of the Chaozhou dialect community during the early Klang period. This paper serves both as a study on Chinese dialect community, and also study of the history of Klang. Keywords: Klang, Chaozhou, Chaozhou dialect community 早年巴生潮州人社群初探 徐威雄 摘要 巴生为巴生谷最早开发的地区，在众多的华族人口中，潮州籍仅占极少数。潮州 人自十九世纪末移居巴生以来，形成一个鲜明的地方社群，他们组织乡团会馆， 参与当地华社文教的建设，并长期操控了巴生杂货米粮行业。本文结合文献史料 与田野调查的考察，从人口移殖、原乡籍贯、行业特色等各方的探讨，勾勒出早 期巴生潮州社群的形成及其面貌。本文为华人方言群研究，也是属于巴生地方史 的研究。 关键词：巴生、潮州人、潮州社群